Microwear textures of Australopithecus africanus and Paranthropus robustus molars in relation to paleoenvironment and diet. Issue 119 (June 2018) - Peterson, Alexandria; Abella, Elicia F.; Grine, Frederick E.; Teaford, Mark F.; Ungar, Peter S.
Abstract: The importance of diet in primate ecology has motivated the use of a variety of methods to reconstruct dietary habits of extinct hominin taxa. Dental microwear is one such approach that preserves evidence from consumed food items. This study is based on 44 specimens of Australopithecus africanus from Makapansgat and Sterkfontein, and 66 specimens of Paranthropus robustus from Swartkrans, Kromdraai and Drimolen. These samples enable examination of potential differences between the two assemblages of A. africanus, and among the various assemblages of P. robustus in relation to the paleoenvironmental reconstructions that have been proffered for each fossil site. Sixteen microwear texture variables were recorded for each specimen from digital elevation models generated using a white-light confocal profiler. Only two of these differ significantly between the Makapansgat and Sterkfontein samples of A. africanus . None of the microwear texture variables differs significantly among the samples of P. robustus . On the other hand, P. robustus has significantly higher values than A. africanus for 11 variables related to feature complexity, size, and depth; P. robustus exhibits rougher surfaces that comprise larger, deeper features. In contrast, A. africanus has smoother, simpler wear surfaces with smaller, shallower and more anisotropic features. As for possible habitat differences among the various sites, only a relatively small number of subtle differences are evident between the specimens of A. africanus from Makapansgat and Sterkfontein, and there are none among the specimens of P. robustus from various deposits. As such, it is reasonable to conclude that, while subtle differences in microwear textures may reflect differences in background habitats, the wear fabric differences between P. robustus and A. africanus are most reasonably interpreted as having been driven by dietary differences.